2023
DOI: 10.1021/acs.est.2c07660
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics and Particle Number-Based Trophic Transfer of a Metallic Nanoparticle Mixture in a Terrestrial Food Chain

Abstract: Herein, we investigated to which extent metallic nanoparticles (MNPs) affect the trophic transfer of other coexisting MNPs from lettuce to terrestrial snails and the associated tissue-specific distribution using toxicokinetic (TK) modeling and single-particle inductively coupled plasma mass spectrometry. During a period of 22 days, snails were fed with lettuce leaves that were root exposed to AgNO 3 (0.05 mg/L), AgNPs (0.75 mg/L), TiO 2 NPs (200 mg/L), and a mixture of AgNPs and TiO 2 NPs (equivalent doses as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The decision to reduce the cell culture time to 4 h, as opposed to maintaining the same duration as the proliferation experiments (120 h), was primarily influenced by the observable decrease in the survival probability and viability of the hemocytes with prolonged coculture time (Figures b and S5c). Our pilot studies, in conjunction with prior research, have consistently recommended that incubation times for freshly isolated hemocytes should not exceed 5 h to ensure result accuracy. , …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The decision to reduce the cell culture time to 4 h, as opposed to maintaining the same duration as the proliferation experiments (120 h), was primarily influenced by the observable decrease in the survival probability and viability of the hemocytes with prolonged coculture time (Figures b and S5c). Our pilot studies, in conjunction with prior research, have consistently recommended that incubation times for freshly isolated hemocytes should not exceed 5 h to ensure result accuracy. , …”
Section: Resultsmentioning
confidence: 89%
“…Our pilot studies, in conjunction with prior research, have consistently recommended that incubation times for freshly isolated hemocytes should not exceed 5 h to ensure result accuracy. 28,49 Notably, pronounced dark/light spots were evident in the hemocytes exposed to NPs, even at the lowest concentration (Figure 3c). Examination through Confocal Laser Scanning Microscopy (CLSM) and TEM images confirmed that these spots corresponded to agglomerates of NPs (Figures 3d and S 5d).…”
Section: Cytotoxicity Of Npsmentioning
confidence: 97%